Acute pancreatitis: Definition, pathophysiology, diagnosis and treatment (Research, Society and Development, 2025)
Acute pancreatitis is an acute inflammatory condition of the pancreas characterized by severe abdominal pain and elevated serum amylase and lipase levels. The most common etiologies are cholelithiasis and excessive alcohol consumption, although factors such as hypertriglyceridemia and the use of certain medications may also contribute. Diagnosis is based on clinical evaluation, laboratory findings, and imaging studies, including computed tomography and ultrasonography. Treatment is primarily supportive, encompassing fluid resuscitation, pain management, and nutritional support. Severe cases may require endoscopic, surgical, or intensive care interventions. Early identification of complications, such as pancreatic necrosis and organ failure, is essential to reduce morbidity and mortality. Recent studies have focused on biomarkers and therapeutic strategies to improve prognosis and individualize treatment. This study aims to review the main aspects of acute pancreatitis, with an emphasis on etiology, pathophysiology, diagnosis, treatment, and prognosis.